Managing brand equity : capitalizing on the value of a brand name - Aaker, David A., 1938- (New York : Free Press ; Maxwell Macmillan International ; Toronto : Maxwell Macmillan Canada, 1991)
The most important assets of any business are intangible: its company name, brands, symbols, & slogans, & their underlying associations, perceived quality, name awareness, customer base, & proprietary resources such as patents, trademarks, & channel relationships. These assets, which comprise brand equity, are a primary source of competitive advantage & future earnings. Few people understand brand equity & how it must be implemented. Provides a clear & well-defined structure of the relationship between a brand & its symbol & slogan, as well as each of the five underlying assets, which clarifies exactly how brand equity does contribute value.
Publikace představuje systematický a vlivný výklad konceptu hodnoty značky (brand equity) jako jednoho z klíčových nehmotných aktiv moderního podniku. Autor vysvětluje, jak značky, názvy, symboly a slogany – spolu s asociacemi, vnímanou kvalitou, znalostí značky a loajalitou zákazníků – vytvářejí konkurenční výhodu a dlouhodobý ekonomický přínos. Kniha nabízí ucelený analytický rámec pro řízení značky, objasňuje vztah mezi značkou a jejími identifikačními prvky a detailně rozpracovává jednotlivé složky brand equity a jejich vliv na hodnotu firmy.
Obsahuje bibliografické odkazy a rejstřík
Keywords: obchodní značky; řízení značky; oceňování obchodní značky; marketingový management; monografie; brand name products; brand management; valuation of brand name products; marketing management; monographs